A novel pathogenesis of inflammatory bowel disease from the perspective of glyco-immunology. (7th March 2017) - Shinzaki, Shinichiro; Iijima, Hideki; Fujii, Hironobu; Kamada, Yoshihiro; Naka, Tetsuji; Takehara, Tetsuo; Miyoshi, Eiji
Abstract : Oligosaccharide modifications play an essential role in various inflammatory diseases and cancers, but their pathophysiologic roles, especially in inflammation, are not clear. Inflammatory bowel disease (IBD) is an intractable chronic inflammatory disorder with an unknown aetiology, and the number of patients with IBD is increasing throughout the world. Certain types of immunosuppressant drugs, such as corticosteroids, are effective for IBD, suggesting that immune function is closely associated with the pathophysiology of IBD. Recent progress in the analysis of oligosaccharides revealed a role for oligosaccharides in intestinal inflammation based on both experimental models and human samples from IBD patients. Moreover, changes in the oligosaccharide structures on glycoproteins in the sera and tissue samples may serve as biomarkers of IBD. Here, we present current studies of IBD with regard to the immunologic aspects of glycobiology, suggesting a novel concept for IBD pathogenesis and the function of oligosaccharides on immune cells, termed "glyco-immunology".